Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12961-022-00932-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of good governance, economic growth and universal health coverage on COVID-19 infection and case fatality rates in Africa

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has disrupted lives across all countries and communities. It significantly reduced the global economic output and dealt health systems across the world a serious blow. There is growing evidence showing the progression of the COVID-19 pandemic and the impact it has on health systems, which should help to draw lessons for further consolidating and realizing universal health coverage (UHC) in all countries, complemented by more substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…This proves that the UHC score fulfills the objective of UHC, based on the coverage in the field of infectious diseases. Furthermore, the result of this study is in line with other studies [ 35 , 36 , 44 ], such that the higher the UHC score, the better the country can deal with the COVID-19 situation than countries with lower UHC scores.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This proves that the UHC score fulfills the objective of UHC, based on the coverage in the field of infectious diseases. Furthermore, the result of this study is in line with other studies [ 35 , 36 , 44 ], such that the higher the UHC score, the better the country can deal with the COVID-19 situation than countries with lower UHC scores.…”
Section: Discussionsupporting
confidence: 90%
“…The second method of analysis is a regression analysis. Recently, researchers have been focusing on the use of the UHC score as an independent variable and defining whether the UHC score has any influence on the infectious and death cases not [ 35 , 36 ]. Furthermore, some studies, including Coccia's [ 67 ], have analyzed the differences in the COVID-19 situation between countries with longer and shorter l lockdown periods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant associations between interpersonal trust and social distancing in Kenya. The different findings are consistent with the idea that communication from acquaintances become more important for protecting health as government action becomes less clear ( Alfano, 2022 ; Gebremichael et al, 2022 ), although additional research is necessary to pinpoint precisely why the two countries differ. Policymakers in Burkina Faso should consider spreading health messages through churches and personal networks because our research reveals those networks are associated with the adoption of healthy behaviors in that country.…”
Section: Discussionsupporting
confidence: 71%
“…This may be related to the less consistent response of the national government to the pandemic in that country ( Mishra, 2020 ). Previous research in Africa has shown that more stringent government action significantly reduced national COVID-19 infection rates ( Gebremichael et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%